2010
DOI: 10.1172/jci42388
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 attenuates Th2 responses to Aspergillus fumigatus mounted by CD4+ T cells from cystic fibrosis patients with allergic bronchopulmonary aspergillosis

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is caused by a dominant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 43 publications
5
119
2
3
Order By: Relevance
“…Previous studies have characterized the T cell response in human CF patients (33,34) (24,26,27,30) (35) and murine P. aeruginosa (36)(37)(38)(39)(40) or Aspergillus fumigatus infection models (41)(42)(43), providing evidence that the adaptive T cell response in CF is altered at several levels. CF T cells were found to be prone to a Th2 phenotype, with the CFTR mutation itself and/or chronic infections with P. aeruginosa as possible underlying factors (42,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have characterized the T cell response in human CF patients (33,34) (24,26,27,30) (35) and murine P. aeruginosa (36)(37)(38)(39)(40) or Aspergillus fumigatus infection models (41)(42)(43), providing evidence that the adaptive T cell response in CF is altered at several levels. CF T cells were found to be prone to a Th2 phenotype, with the CFTR mutation itself and/or chronic infections with P. aeruginosa as possible underlying factors (42,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…AM: alveolar macrophage; DC: dendritic cell; TNF: tumour necrosis factor. Reproduced and modified with permission from [16]; see also [17] and [18] for detailed discussion. assumption arises from several lines of investigation.…”
Section: Antifungal Therapy In Abpa and Safsmentioning
confidence: 99%
“…The pathophysiology of ABPA results from florid T-helper cell (Th)2 innate and adaptive immune responses in susceptible hosts who are unable to efficiently clear the respiratory epithelium of inhaled fungal spores ( fig. 1) [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that the active form of vitamin D (1,25-dihydroxyvitamin D 3 ) can suppress Aspergillus fumigatusspecific Th2 responses in peripheral CD4 ϩ T cells in patients with cystic fibrosis (CF) and allergic bronchopulmonary aspergillosis (ABPA) (10). This suppression of Th2 development was associated with an increase in transforming growth factor ␤-positive (TGF-␤ ϩ ) regulatory T cells as well as suppression of OX40L, a costimulatory molecule regulated by TSLP in vitro (7,10).…”
mentioning
confidence: 99%